A methodology for the analysis of the Rayleigh-wave ellipticity - Corchete, V (Earth Sciences Research Journal, 2013)
In this paper, a comprehensive explanation of the analysis (filtering and inversion) of the Rayleigh-wave ellipticity is performed, and the use of this analysis to determine the local crustal structure beneath the recording station is described. This inversion problem and the necessary assumptions to solve are described in this paper, along with the methodology used to invert the Rayleigh-wave ellipticity. The results presented in this paper demostrate that the analysis (filtering and inversion) of the Rayleigh-wave ellipticity is a powerful tool, for studying the local structure of the crust beneath the recording station. Therefore, this type of analysis is very useful for studies of seismic risk and/or seismic design, because it provides local earth models in the range of crustal depths. Resumen En este artículo, será realizada una explicación fácil de comprender del análisis (filtrado e inversión) de la elipticidad de la onda Rayleigh, así como, de su aplicación para determinar la estructura local bajo la estación de registro. Este problema de inversión y los necesarios supuestos para resolverlo, serán descritos en el artículo, juntamente con la metodología utilizada para invertir la elipticidad de la onda Rayleigh. Los resultados presentados en este artículo mostrarán que el análisis (filtrado e inversión) de la elipticidad de la onda Rayleigh es una poderosa herramienta, para estudiar la estructura local de la corteza terrestre bajo la estación de registro, siendo este tipo de análisis muy útil para estudios de riesgo y/o diseño sísmico, porque proporciona modelos de Tierra locales en el rango de profundidades corticales.